Common institutional ownership and investment efficiency: Empirical evidence from China - Yajie Bai; Leilei He; Zhang Tiegang (Borsa İstanbul Review, 2023)
Common institutional ownership has become a significant form of shareholding in the capital market. Using panel data on 2395 listed companies in China from 2007 to 2020, we examine the investment efficiency of this ownership practice on microcorporate investment behavior. The estimates indicate that common institutional ownership has a significant positive relationship with corporate investment efficiency by reducing overinvestment. Further institutional heterogeneity analysis reveals that enterprises have independent and long-term investment horizon of common institutional investors, and the positive effect of common institutional ownership on enterprises' investment efficiency is stronger. The empirical results are validated by a series of robustness tests. This study provides empirical support for the performance of common institutional ownership participating in corporate governance and optimizing investment decisions.
Keywords: G32; G34; L22; 330; Capital market; Common institutional ownership; Institutional heterogeneity; Investment efficiency